Aesthetics and Utilitarian Essence of Selected Yorùbá Folktales - Omolaye, Bamidele Vincent (Journal of Advanced Research in Humanities and Social Sciences, 2022)
Folktales constitute one of the oldest traditional forms of education based on the method of delivery through oral tradition. Among the Yorùbá, folktale is a viable medium for transmission of cultural values, belief, history and philosophy of the society to the younger generation. The fact that customs, morals and way of life of the African societies in general, are found to be ingrained and codified in folktales, shows the veracity of the indigenous knowledge system (IKS) embedded therein. This has contributed immensely to appreciating the culture, as well as the social norms of the African societies. This study examines the aesthetics and utilitarian essence of African folktales, using four purposively selected Yorùbá folktales as case study. This is with a view to revealing the aesthetics and usefulness of African folktales and documenting the songs therein in a staff notation for musical analysis. Data for the study were gathered through oral interviews and review of related literature. The selected Yorùbá folktales were examined through descriptive method. Findings show that the essence of African folktales, as noticed in this present day, is being jettisoned and gradually going into extinction by the current realities brought about by globalisation. This has greatly affected the cultural values which African folktales retain, maintain and disseminate. Hence, the need for the revitalisation and digitisation of African folktales, in order to preserve the indigenous knowledge system deep-rooted in the narratives for future generations. This study concludes that the importance of African folktales would be better understood if properly harnessed, translated and notated from the musicological viewpoint, as it will further popularise the old tradition of storytelling in this modern age. How to cite this article: Omolaye B. Aesthetics and Utilitarian Essence of Selected Yorùbá Folktales. J Adv Res Humani Social Sci 2022; 9(4): 8-18.